Effects of nerve regeneration therapy on functional recovery after nerve injury - Sung, Youn-Bum; Lee, Jung-Ho (International Journal of Engineering and Technology, 2019)
The purpose of this study was to investigate the effects of treadmill exercises utilizing CIMT as performed by white rats, in which crushed sciatic nerves were induced, by time of measurement through neurological motor-behavior tests. The rats were randomly assigned to a control group, a CIMT group, and an exercise group after being affected by sciatic nerve damage. To evaluate the effects of the nerve regeneration therapy on motor nerves, the SFI of rats across all groups were measured after application of the treatment. The ladder walking test was used to measure the degrees of deficit or recovery of sensory functions. To analyze gait behavior following sciatic nerve damage recovery, the gait behaviors of rats in all groups were measured using the Dartfish program after application of the treatment. As the result, there was no statistically significant difference in all groups at 1, 7 days (p>.05), but there was a significant difference at 14, 21 days on SFI, ladder rung walking test, and ankle angle. In conclusion, the combined use of CIMT and exercise therapy had the greatest positive effect on nerve recovery after nerve injury.Â